China’s Export Reform Strategy in Response to the United States National Defense Authorization Act of 2019 - Naoka Zayna Treasa; Shanti Darmastuti (Insignia: Journal of International Relations, 2025)
The enactment of the United States’ National Defense Authorization Act (NDAA) 2019, particularly Article 889, created significant non-tariff pressure on China’s high-tech export sector by restricting the procurement and use of products from major Chinese technology firms. This situation raised concerns about China’s export vulnerability and the long-term implications of geopolitical trade tensions. This study aims to examine China’s export reform strategies formulated in response to the NDAA, focusing on institutional coordination, financial support mechanisms, fiscal incentives, and the development of high-tech industrial ecosystems. Using a descriptive qualitative method, data were collected through literature review of policy documents, academic publications, and official reports, complemented by interviews with a China political expert and an Indonesian diplomat specializing in Asia–Pacific economic affairs. The findings reveal that China’s policy adjustments were not reactive measures but components of a long-term industrial strategy. The National Development and Reform Commission (NDRC) played a central coordinating role in aligning fiscal, industrial, and diplomatic instruments. Strengthened financing through Sinosure and the Export-Import Bank of China, combined with increased export tax rebates and industrial zone incentives, enabled high-tech firms to diversify markets and sustain competitiveness. The study concludes that China’s export reform reflects a strategic model of state-led resilience, demonstrating how coordinated institutional policies can mitigate external trade shocks and maintain export stability amid intensifying geopolitical competition. Keywords: China, export support, NDAA 2019, non-tariff protectionism